Deteksi Karakteristik Peluruhan Radionuklida Medis 99Mo Untuk Memperoleh 99mTc Menggunakan Spektrometer Gamma dengan Sumber Standar Cair Campuran 133Ba dan 152Eu - Mawar - Mawar; Sri Dewi Astuti; Siska Febriana (Department of Physics Universitas Gadjah Mada, 2020)
Technetium-99m (99mTc) is a subsidiary of metastable 99Mo with a half-life of 6 hours. The relatively short half-life, causing 99mTc widely used for diagnostic purposes in nuclear medicine, especially in bone scanning for a faster decay. This research aims to determine the optimal time to product formation of 99mTc until elution profiles have detected 99Mo energy. The instrument used is the 99Mo/99mTc generator with standard sources 133Ba and 152Eu liquid mixture. The results obtained showed that 99mTc radioisotope production is still good until the third day elution 99Mo, whereas in the fourth to ninth day 99Mo energy detected on the decline, so that the activity of the 99mTc resulting product cannot be used for diagnosis.